2021
DOI: 10.3390/v13050741
|View full text |Cite
|
Sign up to set email alerts
|

Three Strains of Tobacco etch virus Distinctly Alter the Transcriptome of Apical Stem Tissue in Capsicum annuum during Infection

Abstract: Tobacco etch virus (TEV; genus Potyvirus) is flexuous rod shaped with a single molecule of single-stranded RNA and causes serious yield losses in species in the Solanaceae. Three TEV strains (HAT, Mex21, and N) are genetically distinct and cause different disease symptoms in plants. Here, a transcriptomic RNA sequencing approach was taken for each TEV strain to evaluate gene expression of the apical stem segment of pepper plants during two stages of disease development. Distinct profiles of Differentially Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This result indicates that a large quantity of transcriptional changes occurred during CVB-CN infection. This finding corroborates with those of previous studies wherein it was observed that host plants extensively alter their gene expression in response to viral infections [ 49 , 75 , 78 ]. GO enrichment analysis revealed that the CVB-CN responsive SDEGs were predominantly involved in the “Unsaturated fatty acid biosynthetic process”, “Secondary metabolite biosynthetic process”, “Transcription”, “Actin filament organization”, “Translation”, and “Regulation of transcription” in the biological process category (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result indicates that a large quantity of transcriptional changes occurred during CVB-CN infection. This finding corroborates with those of previous studies wherein it was observed that host plants extensively alter their gene expression in response to viral infections [ 49 , 75 , 78 ]. GO enrichment analysis revealed that the CVB-CN responsive SDEGs were predominantly involved in the “Unsaturated fatty acid biosynthetic process”, “Secondary metabolite biosynthetic process”, “Transcription”, “Actin filament organization”, “Translation”, and “Regulation of transcription” in the biological process category (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In the past decade, the availability of transcriptome data from host plants in response to RNA viruses has dramatically expanded. For example, data sets from the leaves of N. tabacum systemically infected with the M strain of CMV (M-CMV) with 8513 DEGs were generated by Lu et al [ 75 ]; from the leaves of D. grandiflorum in response to CMV, tomato spotted wilt virus (TSWV), and PVX with 124 DEGs were produced by Choi et al [ 76 ]; from the leaves of L. regale in response to CMV with 1346 DEGs were reported by Sun et al [ 64 ]; from the leaves of P. vulgaris in response to soybean mosaic virus with 3548 DEGs were identified by Zhang et al [ 77 ]; and from stems of C. annuum in response to three tobacco etch virus strains HAT, Mex21, and N having 24, 1190, and 4010 DEGs, respectively, were published by Murphy et al [ 78 ]. However, to the best of our knowledge, transcriptome data on the mechanisms underlying the response of chrysanthemum to CVB are still not available.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, genes of ascorbate biosynthesis pathways revealed specific strain responses to apical stems infected with three tobacco etch virus (TEV) strains (HAT, Mex21, and N) at 7 and 14 days post-inoculation (dpi) (PRJNA476480) [42]. The infection caused by severe N strain, negatively affected the expression of genes from L-galactose, myo-inositol, and L-gulose pathways, mainly at 14 dpi (Figure 10 and Table S10).…”
Section: Expression Profile Of Genes Of Ascorbate Biosynthesis Under ...mentioning
confidence: 99%